Crowdsourced Starlink Performance Measurements from https://starlinkstatus.space - Bülo, Manuel; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (ICC 2024 - IEEE International Conference on Communications, 2024)
Starlink is the largest and most powerful low Earth orbit satellite megaconstellation built to date. Since its debut in 2021, there has been an enormous interest in performance evaluations. https://starlinkstatus.space is a crowdsourced measurement platform based on the Ookla speed test. This paper presents its design, user statistics, and results: Almost 1.7 million measurements from 309 users and 29 countries. The median goodput rates are between 100 Mbit/s and 200 Mbit/s in the forward link (download), and between 10 Mbit/s and 20 Mbit/s in the return link (upload). Goodput rates in North America are lower than in other countries, and the time of day matters, with peak time performance down to a median of 50 Mbit/s. Median round trip times are between 40 ms and 50 ms. Latency under load seems to have improved recently. The hardware version of the standard user terminal does not seem to have an impact on the performance.<br